Bearers of culture: images of veiling in Marjane Satrapi’s Persepolis - Jelodar, Esmaeil Zeiny; Noraini Md. Yusof; Khalil Mahmoodi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Much ink has been spilled on the history of veiling, reveiling, and unveiling in various parts of the Muslim world, particularly in Iran. However, little mention is given in most scholarly works as to how it affects women and its ramifications in society. By examining the history of veiling in Iran and the study of veiling as represented in Marjane Satrapi’s memoir, Persepolis, this paper sheds light on the ramifications of forced unveiling and veiling, and it also enlightens the readers to how the Iranian women became the yardstick with which the country’s progress is measured. We argue that the two Acts of Unveiling and Veiling have been a mechanism in the service of patriarchy, which created division, conflict and segregation amongst women. We also argue that unlike the public perception that veiling is a phenomenon for Islamic hegemony and a heritage of Arab conquest, Persian women have used veiling centuries before the emergence of Islam, and in modern Iran, voluntary veiling can be used as a cultural sign of anti-imperialism.